2005
DOI: 10.1179/174329305x64303
|View full text |Cite
|
Sign up to set email alerts
|

Original surface treatment of copper alloy in ancient Roman Empire: Chemical patination on a Roman strigil

Abstract: Metal polychromy has been widely used for decorating metallic artworks from ancient antiquity. In Hellenistic and Roman periods, the famous Corinthian bronzes (Corinthium aes) are a typical example of the skill of metallurgical craftsmen striving to obtain various coloured surfaces on copper based alloys; but the existing investigations are devoted mainly to the 'black bronzes' obtained by oxidation in a wet medium of copper-gold alloys. The present study is part of a general programme devoted to research into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Although bronze patinas are widely found in cultural heritage objects, they are normally characterised based on their chemical composition, using analytical methods such as X-ray diffraction, particle induced X-ray emission [1], Raman microscopy [6], scanning electron microscopy [7] and others [8]. To the authors knowledge, there have not been extensive works on the characterisation of the visual appearance of bronze patinas using imaging techniques.…”
Section: Visual Appearance In Cultural Heritagementioning
confidence: 99%
See 1 more Smart Citation
“…Although bronze patinas are widely found in cultural heritage objects, they are normally characterised based on their chemical composition, using analytical methods such as X-ray diffraction, particle induced X-ray emission [1], Raman microscopy [6], scanning electron microscopy [7] and others [8]. To the authors knowledge, there have not been extensive works on the characterisation of the visual appearance of bronze patinas using imaging techniques.…”
Section: Visual Appearance In Cultural Heritagementioning
confidence: 99%
“…Patinas are a form of metal polychromy widely used to decorate metallic artworks. They allow craftsmen to obtain various coloured surfaces on copper-based alloys by applying chemical treatments which build a compound layer on the surface [1]. In this work, the patinas used were made by the Coubertin foundry, located in the outskirts of Paris.…”
Section: Introductionmentioning
confidence: 99%
“…A number of publications have presented the major element analysis of black bronze artefacts (Craddock 1982;Murakami et al 1988;La Niece 1991;Giumlia-Mair and Craddock 1993;Wayman and Craddock 1993;Photos 1994;Demakopoulou et al 1995;Giumlia-Mair 1995Stapleton et al 1995;Caple and Clogg 2001;Mathis et al 2005Mathis et al , 2009Aucouturier et al 2010;Mohamed and Darweesh 2012). It is generally agreed that black bronze owes its appearance to a fine, compact and resistant patina developed on its surface.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to reconcile historical recipes with modern materials and processes, and with archaeological artefacts, can lead to dubious correspondences (Martinón‐Torres and Rehren ). For this reason, the modern literature on the history of black bronze alloys highlights the need for more detailed technical analyses on archaeological or historical artefacts, which may allow reverse engineering of their manufacture (e.g., Whitfield ; Giumlia‐Mair , ), as well as for a better understanding of the material in itself and the patination mechanisms, achievable through experimental tests (Mathis et al ).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 A complete review may be found elsewhere. 5 The typological observations done by the first Egyptologists 9 were not sufficient to define precisely the typical black bronzes, and a rigorous definition was given through physicochemical studies, 5,10,11 which provided scientific criteria to identify definitely the intentionally patinated black bronzes and differentiate them from pieces neither intentionally patinated nor possibly patinated with another recipe: 1,10,12 the patina is a cuprite (Cu 2 O) layer containing Au and/or Ag.…”
Section: Introductionmentioning
confidence: 99%